Degenerated fibroid - a diagnostic challenge - Bhuyar, Sonal; Sontakke, Bhavana; Rajbhara, Pooja Mukund (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Leiomyoma of the uterus is the most common type of tumor affecting the female pelvis and arises from uterine smooth muscle. The size of leiomyoma varies from microscopic to giant; giant myoma is exceedingly rare. We report an unusual case of a large, cystic, uterine leiomyoma mimicking a primary malignant ovarian tumor on sonography and CT. A 39 year old infertile nulliparous woman presented with a history of lump in abdomen since 2 years and 6 months of amenorrhea. Sonography and CT examination showed a large mass that filled the abdomen. A preoperative diagnosis of a primary malignant ovarian tumor was made. The patient underwent laparotomy with total abdominal hysterectomy preserving tubes and ovaries. The histology revealed a leiomyoma with extensive hyaline degeneration. The current established management of uterine fibroids may include expectant, surgical, or medical management or uterine artery embolization or a combination of these treatments. A surgical approach is preferred for management of giant leiomyomas. Leiomyomas should be considered in the differential diagnosis of a multilocular and predominantly cystic adnexal mass.